Inhibition of Lysyl Oxidases Impairs Migration and Angiogenic Properties of Tumor-Associated Pericytes - Aline Lopes Ribeiro; Carolini Kaid; Patrícia B. G. Silva; Beatriz A. Cortez; Oswaldo Keith Okamoto (Stem Cells International)
Pericytes are important cellular components of the tumor microenviroment with established roles in angiogenesis and metastasis. These two cancer hallmarks are modulated by enzymes of the LOX family, but thus far, information about LOX relevance in tumor-associated pericytes is lacking. Here, we performed a comparative characterization of normal and tumoral pericytes and report for the first time the modulatory effects of LOX enzymes on activated pericyte properties. Tumoral pericytes isolated from childhood ependymoma and neuroblastoma specimens displayed angiogenic properties in vitro and expressed typical markers, including CD146, NG2, and PDGFRβ. Expression of all LOX family members could be detected in both normal and tumor-associated pericytes. In most pericyte samples, LOXL3 was the family member displaying the highest transcript levels. Inhibition of LOX/LOXL activity with the inhibitor β-aminopropionitrile (βAPN) significantly reduced migration of pericytes, while proliferation rates were kept unaltered. Formation of tube-like structures in vitro by pericytes was also significantly impaired upon inhibition of LOX/LOXL activity with βAPN, which induced more prominent effects in tumor-associated pericytes. These findings reveal a novel involvement of the LOX family of enzymes in migration and angiogenic properties of pericytes, with implications in tumor development and in therapeutic targeting tumor microenvironment constituents.